Evaluation of Contamination and Accumulation of Heavy Metals in the Dhaleswari River Sediments, Bangladesh - Mamun, Abdullah Al; Sarker, Protima; Rahaman, Md. Shiblur; Kabir, Mohammad Mahbub; Maruo, Masahiro (International Journal of Environment, 2021)
The Dhaleswari river is considered as one of the most important rivers of Bangladesh due to its geographical location and ecological services. The present study attempts to evaluate the degree of heavy metal pollution, contamination, and accumulative behavior in the sediment of the Dhaleswari river. The sediment samples were collected from fifteen different locations of the Dhaleswari river. Heavy metals were analyzed using the Flame Atomic Spectrophotometer (FAAS). The mean concentrations of Zn, Cu, Cr, Pb and Cd were 131.9, 48.89, 43.16, 33.23 and 0.37 mgkg-1, respectively. According to the United States Environmental Protection Agency (USEPA) Sediment Quality Guideline, the sediment of most of the locations were not polluted for Pb and Cd. But S-11 location for Cd (0.8 mg kg-1) was highly polluted. For Cr, Cu and Zn, maximum locations were moderately polluted. Although the geo-accumulation index (Igeo) values of Dhaleswari river sediments showed almost no severe contamination for most of the sampling locations, the pollution load index (PLI) values showed that most of the sampling sites were contaminated for all heavy metals tested. Moreover, for all measured heavy metals, the mean Contamination Factor (CF) values indicated moderate pollution, except for Cr, which suggested low pollution. The Pearson’s correlation coefficient matrix among the selected heavy metals of Dhaleswari river sediment showed no significant correlation among each other. Therefore, regular monitoring of the heavy metal concentration of the Dhaleshwari river sediment from different location is necessary to identify the sources of pollution so that proper initiative could be taken to prevent heavy metal pollution.